Responses by general practitioners in Avon to proposals for general practice in the white paper Working for Patients. Issue 6682 (6th May 1989) - Whitfield, M.; Wood, N.; Wright, F.
Abstract : OBJECTIVE--To determine the views of Avon's general practitioners about the general practice proposals within the government's white paper Working for Patients. DESIGN--Postal questionnaire survey. SETTING--A county in south west England. SUBJECTS--All general practitioner principals (n = 537) under contract with Avon Family Practitioner Committee. MEASUREMENTS AND MAIN RESULTS--492 doctors (92%) responded to the survey. More than three quarters of the respondents were opposed to the government's proposals on budgets for specific surgical procedures, prescribing, and diagnostic tests; and between 63% and 93% felt negative about advantages that might accrue from the proposals. Over three quarters of general practitioners were in favour of family practitioner committees monitoring work load, prescribing, and referrals. General practitioners in large, potentially budget holding practices held similar views to doctors in smaller practices. CONCLUSIONS--Avon's general practitioners substantially reject most of the government's proposals about general practice in the white paper Working for Patients.